Pengaruh Tata Kelola Perusahaan, Struktur Aset, Kepemilikan Institusional dan Kepemilikan Manajerial terhadap Manajemen Laba Riil: Bukti dari Perusahaan Energi di Indonesia - Heri Dwi Agung Laksono; Agrianti Komalasari (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to examine the effect of corporate governance, asset structure, institutional ownership, and managerial ownership on real earnings management in energy sector companies listed on the Indonesia Stock Exchange. The study is motivated by the increasing concern regarding the quality of financial reporting and the tendency of managers to engage in real earnings management through operational decisions that are difficult to detect. This study employs a quantitative approach using panel data derived from annual reports and financial statements of energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The data are analyzed using panel data regression techniques to identify the relationship between corporate governance, asset structure, institutional ownership, managerial ownership, and real earnings management. The findings are expected to provide empirical evidence regarding the role of monitoring mechanisms and ownership structure in influencing real earnings management practices, as well as providing implications for investors, regulators, and corporate stakeholders regarding the importance of effective governance mechanisms and ownership structures in improving financial reporting quality and reducing opportunistic managerial behavior. This study integrates Agency Theory and Resource Dependence Theory to explain real earnings management behavior in Indonesian energy companies. Furthermore, it focuses on the energy sector, which has received relatively limited attention in real earnings management studies despite its strategic importance and unique operational characteristics.